1996
DOI: 10.1523/jneurosci.16-01-00082.1996
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of intracellular Cl- levels by Na(+)-dependent Cl- cotransport distinguishes depolarizing from hyperpolarizing GABAA receptor-mediated responses in spinal neurons

Abstract: Rohon-Beard (RB) spinal neurons of Xenopus larvae are depolarized by GABA. To study the mechanisms underlying this distinctive response, intracellular and patch-clamp recordings were made from RB neurons in situ. The intracellularly recorded GABA reversal potential (EREV) was near -30 mV in normal saline and was approximately 25 mV more negative in Na(+)-free saline. Whole-cell recordings from RB neurons and from neighboring dorsolateral interneurons (DLi) revealed that GABA responses of both cells were mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
147
0
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(168 citation statements)
references
References 53 publications
20
147
0
1
Order By: Relevance
“…Consistent with previous studies, bumetanide reduced the GABA-induced membrane depolarization in VS-3 neurons by 6.7 mV. For example, tadpole Rohon-Beard neuron reversal potential for GABA was about 10 mV (Rohrbough and Spitzer 1996) and rat hippocampal neurons about 18 mV more negative after bumetanide treatment (Sipilä et al 2006). In previous studies Values in each cell are means Ϯ SD.…”
Section: Chloride Transporters Do Not Reduce the Excitatory Effect Ofsupporting
confidence: 89%
See 1 more Smart Citation
“…Consistent with previous studies, bumetanide reduced the GABA-induced membrane depolarization in VS-3 neurons by 6.7 mV. For example, tadpole Rohon-Beard neuron reversal potential for GABA was about 10 mV (Rohrbough and Spitzer 1996) and rat hippocampal neurons about 18 mV more negative after bumetanide treatment (Sipilä et al 2006). In previous studies Values in each cell are means Ϯ SD.…”
Section: Chloride Transporters Do Not Reduce the Excitatory Effect Ofsupporting
confidence: 89%
“…This secondary active transporter is also responsible for the high intracellular Cl Ϫ gradient in amphibian dorsal root ganglion neurons and Rohon-Beard neurons, which respond to GABA A receptor activation with depolarization (Alvarez-Leefmans et al 1988, 2001Rohrbough and Spitzer 1996). Consistent with previous studies, bumetanide reduced the GABA-induced membrane depolarization in VS-3 neurons by 6.7 mV.…”
Section: Chloride Transporters Do Not Reduce the Excitatory Effect Ofsupporting
confidence: 81%
“…However, this study does not address the mechanism by which this factor regulates intracellular chloride concentration. Possible mechanisms include regulation of a large number of proteins, including cation-chloride cotransporters (12), namely the Na + -K + -2Cl − cotransporters that increase [Cl − ] i (10,(31)(32)(33)(34)(35) (42), and a variety of chloride channels (13). In contrast to the hippocampus, RGCs do not express Na + -K + -2Cl − cotransporter 1 (23) and they do not express Cl − /HCO 3 + exchangers until later in development (43).…”
Section: Discussionmentioning
confidence: 99%
“…These results suggested that neuronal development might be mediated by the GABA A receptors containing the α2 and α3 subunits, and the GABAergic inhibitory transmission is mediated by the receptors including the α1 and α6 subunits. Although it is generally considered that the changes in GABAergic roles may be reflected by the Cl -reversal potential [10,45,47,52,53], the above suggested that the subunit-composition might partially related to the expression of roles.…”
Section: Relationship Between Gabaergic Roles In the Developing Cerebmentioning
confidence: 99%